2003
DOI: 10.3354/meps246173
|View full text |Cite
|
Sign up to set email alerts
|

Food resource partitioning and competition among alvinellid polychaetes of Juan de Fuca Ridge hydrothermal vents

Abstract: Biotic communities in highly variable, frequently perturbed habitats are usually expected to be structured mainly by abiotic factors. In the highly variable deep-sea hydrothermal vent environment, physical and chemical factors are known to play an important role in limiting the distribution and abundance of species, but the importance of biotic interactions remains largely unresolved. The high density and biomass attained by the vent macrofauna suggest that resource partitioning and competition may be signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 42 publications
4
45
0
Order By: Relevance
“…Other stable isotope studies have reported evidence for generalist feeding (Levesque et al 2003) in these 2 species, as well as a case of apparently exclusive feeding on a chemoautotrophic microbial food source (Limén et al 2007). Behavioural studies have shown P. sulphincola to limit its feeding activity to sulphide mineral surfaces around its tube opening and the tubes of neighbouring conspecifics (Morineaux et al 2002, Grelon et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other stable isotope studies have reported evidence for generalist feeding (Levesque et al 2003) in these 2 species, as well as a case of apparently exclusive feeding on a chemoautotrophic microbial food source (Limén et al 2007). Behavioural studies have shown P. sulphincola to limit its feeding activity to sulphide mineral surfaces around its tube opening and the tubes of neighbouring conspecifics (Morineaux et al 2002, Grelon et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that P. sulfincola has a mixed diet typical of generalist feeding (Levesque et al 2003). The palm worm P. palmiformis is also known to have a varied diet (Levesque et al 2003), and can occur sympatrically with P. sulfincola under less severe hydrothermal conditions (Sarrazin et al 1999). Another siphonostomatoid copepod species, Benthoxinus spiculifer (Humes 1984), is also found on sulphide chimneys in habitats dominated by less severe fluid flows, where P. palmiformis is present (Tsurumi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In hydrothermal vent habitats, unpredictable fluctuations in the physico-chemical environment (e.g. temperature, O 2 , H 2 S) (Johnson et al 1988, Chevaldonne et al 1997, Sarrazin et al 1997, Tivey et al 2002, as well as variations in habitat complexity (Kelly & Metaxas 2008b), available substratum space (Tsurumi & Tunnicliffe 2003) or access to food resources (Levesque et al 2003 site could result in variations in growth of settlers, influencing subsequent recruitment. In addition, the low elasticities observed for P i and F i also indicate that processes such as predation or competition occurring during the post-settlement stages would be more important to the population dynamics of L. fucensis than those occurring during adult life.…”
Section: Lepetodrilus Fucensis Demographymentioning
confidence: 99%